An analysis on the suitability of selected newspaper material as a teaching resource in efl courses. - Sánchez, William (2010)
For this thesis work, first, I collected the scientific material for the Theoretical Background’s section; second, for the Field Research, I collected newspaper material; and third, the Description and Analysis of Results for the final presentation of this thesis work was done. For this, prestigious newspapers from USA and England were employed. Also, in most of this newspaper material, I found formalism as an important part of these newspapers’ culture, showing the way of life of the people where this language comes from.